2008
DOI: 10.1007/s11060-008-9754-7
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged and severe thrombocytopenia with pancytopenia induced by radiation-combined temozolomide therapy in a patient with newly diagnosed glioblastoma—analysis of O 6-methylguanine-DNA methyltransferase status

Abstract: We report a case of a 51-year-old woman with newly diagnosed glioblastoma multiforme (GBM) who was treated with surgery followed by the standard concomitant temozolomide (TMZ) and radiotherapy (RT). Although TMZ is generally safe and well-tolerated, she developed a sudden onset of prolonged and severe thrombocytopenia as the most prominent event of pancytopenia during the combined treatment, leading to discontinuation of the combined therapy. Thrombocytopenia lasted for more than 2 months with intensive, inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
2
15
0
Order By: Relevance
“…However, the role of methylated MGMT gene promoter status and excessive hematological toxicities could not be consistently demonstrated. [14,21,72,73]. Two small studies identified an association between genotype polymorphism and higher risk for TMZ-related profound myelosuppression [21,72].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the role of methylated MGMT gene promoter status and excessive hematological toxicities could not be consistently demonstrated. [14,21,72,73]. Two small studies identified an association between genotype polymorphism and higher risk for TMZ-related profound myelosuppression [21,72].…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed 21 cases of TMZ-related hematological IDRs, including one case of grade V myelosuppression, which we encountered at our center [5,6,[9][10][11][12][13][14][15][16][17][18][19][20][21] (Table 1). Information about sex was available for 16 cases; there were 12 female and four male patients.…”
Section: Hematological Idiosyncratic Drug Reactionsmentioning
confidence: 99%
“…Nagane et al [3], Jalali et al [2] and Singhal et al [4] report a total of 4 cases with long-lasting myelosuppression after temozolomide (one patient has died of sepsis).…”
Section: Discussionmentioning
confidence: 99%
“…The case was investigated for a possible relationship between methylguanine-DNA methyltransferase status and pancytopenia. However, Nagane et al [11] found out that there is not a remarkable relationship between methylguanine-DNA methyltransferase status and pancytopenia.…”
Section: Discussionmentioning
confidence: 99%